Pedagogical and Psychological Features of Scientific and Methodological Supervision in the Professional Development of Teachers - Ibragimov Alamjon Amrilloevich; Khudoyberdiev Eldor Uktamjonovich (International Journal on Integrated Education, 2021)
The article describes the pedagogical and psychological features of scientific and methodical observation in the professional development of teachers, the specificity of scientific and methodical observation among the forms of observation and the importance of continuous teacher education system. The types, forms and content of scientific and methodological observation are described.